Full Content-based Web Page Classification Methods by using Deep Neural Networks - Suleyman Suleymanzade; Fargana Abdullayeva (Statistics, Optimization & Information Computing, 2021)
The quality of the web page classification process has a huge impact on information retrieval systems. In this paper, we proposed to combine the results of text and image data classifiers to get an accurate representation of the web pages. To get and analyse the data we created the complicated classifier system with data miner, text classifier, and aggregator. The process of image and text data classification has been achieved by the deep learning models. In order to represent the common view onto the web pages, we proposed three aggregation techniques that combine the data from the classifiers.